High-Responsivity Ultraviolet Photodetectors With Enhancement of Optical Absorption Using Graphene Components and Al2O3 Layer on Si Substrate - Jangra, Richa; Mishra, Satyendra K.; Sharma, Anuj K. (IEEE sensors journal, 2024)
We report on high-responsivity photodetector (PD) designs with Si substrate, Ag layer, graphene (Gr) components, and Al2O3 layer through enhancement of ultraviolet (UV) light absorption. The finite-difference time-domain (FDTD) method is used for PD simulation under normal incidence of UV radiation. The results indicate that with Si-Ag-Gr PD design, an Al2O3 layer (15-nm thick) considerably increases the absorption causing greater magnitudes of quantum efficiency ( η {)} and responsivity ( ρ {)} in the ultraviolet B (UVB) region (wavelength range: 280-320 nm). In terms of magnitudes, the Si-Ag-Gr-Al2O3 (15 nm) PD design operating at 296.06-nm wavelength ( λ _{{0}}{)} achieves η and ρ as large as 0.628 and 0.149 A/W, respectively. At λ _{{0}} = 296.06 nm, the magnitude of photocurrent ( I_{p}{)} is 64 ~μ \text{A} and the UV-to-visible rejection ratio ( R_{r}{)} is 0.4× 10^{{2}} . Furthermore, the use of reduced graphene oxide (rGO) is explored to operate the PD in the ultraviolet A (UVA) region (wavelength range: 320-370 nm) with equally high performance. The simulation results indicate that Si-Ag-rGO-Al2O3 (1 nm) PD design operating at 336.86-nm wavelength provides η and ρ as large as 0.586 and 0.159 A/W, respectively. At λ _{{0}} = 336.86 nm, the magnitude of I_{p} is 68.23 ~μ \text{A} and R_{r} is 0.26× 10^{{2}} for this PD. These UVA- and UVB-specific PD designs (particularly, Gr-based with 99.6% absorption in the UVB region) possess exceptionally large magnitudes of absorbance, which is an indicator of the perfect absorber behavior of the proposed multilayer designs. The proposed PD design can provide superior responsivity compared to recently reported UV PDs.